Evolution of mechanical and rockburst parameters of gypsum-like rock under fatigue stress disturbance - Chongyang Wang; Sijiang Wei; Dongming Zhang; Beichen Yu; Yisha Pan; Xunjian Hu (Rock Mechanics Bulletin)
To investigate the deterioration of mechanical properties in engineering rock masses subjected to fatigue stress, this study conducted laboratory tests, theoretical analysis, and model building to analyze the evolution of mechanical and rockburst characteristics in gypsum-like rock before and after fatigue loading. The results showed that the effects of cyclic stress and loading frequency on fatigue damage characteristics of the samples are interrelated. The effect of fatigue cyclic stress on the mechanical parameters and rockburst parameters of the samples after fatigue loading is relatively straightforward, while the impact of frequency on the mechanical properties of samples after fatigue loading is more complex. The impact of frequency on mechanical properties and rockburst parameters varies distinctly under different cyclic stress conditions. A deterioration index model (λ=p+jq) was established for the samples after fatigue loading, and the real part, imaginary part, and |λ| of the model were calculated to plot the function in the complex plane. This model provided insight into the evolution of mechanical properties and rockburst characteristics in gypsum-like rock before and after fatigue loading with different stress levels and frequencies. By examining the λ curve’s position within the complex plane, the overall variation in mechanical properties was assessed. Finally, neural network methods were employed to extend and test the complex plane model, expanding the input factors from discrete data points to continuous definition fields on the number line, thereby increasing the model's practicality and applicability.